2002
DOI: 10.1002/cncr.10340
|View full text |Cite
|
Sign up to set email alerts
|

Can initial prostate specific antigen determinations eliminate the need for bone scans in patients with newly diagnosed prostate carcinoma?

Abstract: Type 1 diabetes is considered to be an autoimmune disease in which T lymphocytes infiltrate the islets of pancreas and destroy the insulin producing beta cell population. Besides antigen specificity, the quality of immune reactivity against islet cell antigen(s) is an important determinant of the beta cell destruction. Much evidence indicates that the function of the gut immune system is central in the pathogenesis, as the regulation of the gut immune system may be aberrant in type 1 diabetes. The role of viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 129 publications
3
22
1
Order By: Relevance
“…In Japan, a multicenter retrospective study suggests the incidence of positive bone scanning in patients with low PSA levels is much higher than that in other studies conducted in North America and Europe [8]. According to mass population screening in Korea, the distribution of serum PSA values in Koreans was different from that obtained in Caucasians [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, a multicenter retrospective study suggests the incidence of positive bone scanning in patients with low PSA levels is much higher than that in other studies conducted in North America and Europe [8]. According to mass population screening in Korea, the distribution of serum PSA values in Koreans was different from that obtained in Caucasians [9].…”
Section: Introductionmentioning
confidence: 99%
“…The false-positive rate was higher in our study (20%) than in previous studies, 12,13 perhaps due to the higher percentage of patients with bone metastasis in our study. However, other studies have reported even higher percentages of bone metastasis, including studies by Al-Ghazo and colleagues 15 (98 patients, 39.7% had bone metastasis), Lai and colleagues 16 (116 patients, 29.3% with metastasis), Kosuda and colleagues 17 (1294 patients, 22% with metastasis), and Lee and colleagues 11 (579 patients, 14.3% with metastasis). Therefore, the percentage of bone metastasis in our study was not unusually high.…”
Section: Discussionmentioning
confidence: 91%
“…18 PSA ≤10; 16 PSA ≤10 or Gleason grade ≤2 or GS ≤6; 17 and PSA ≤20 and GS ≤6. 19 However, other reports have suggested that some patients with low PSA and GS had bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Bone scans are commonly obtained even for patients in lowand intermediate-risk categories [70]; however, studies have shown that patients who have PSA levels of 20 ng/mL or less and a Gleason score lower than 8 have a 1% to 13% rate of positive bone scans [71,72]. Other studies have confirmed that in patients who have low PSA levels (<10 ng/mL) and no skeletal symptoms, the yield of bone scanning is too low to warrant its routine use unless the patient has stage T3 or T4 disease or a high Gleason score [73][74][75]. Therefore, a PSA level of greater than 15 to 20 ng/mL is usually used as the cutoff point for obtaining a bone scan, but patients who have skeletal symptoms and those who have a high Gleason score or advanced stage should also be assessed with bone scans.…”
Section: Radionuclide Bone Scintigraphymentioning
confidence: 97%